Infectious Causes of Infertility in Buffalo Bull (Bubalus bubalis) - Perumal, P.; Chamuah, J. K.; Srivastava, N.; Vupru, Kezhavituo; Srivastava, S. K. (International Journal of Bio-resource and Stress Management, 2023)
The artificial insemination (AI) technique plays important roles in improvement of conception rate, prevention of sexually transmitted diseases and carryout of genetic material to next generation. The breeding soundness evaluation (BSE) plays an important step in selection of buffalo bull for the said above purpose. This evaluation is an effective, inexpensive and easy method for selection of breeding buffalo bull. In buffalo breeding management programme, the seasonal variation, nutrition, congenital defect, hormonal changes and hereditary plays a critical role in determining the reproductive efficiency in buffalo bull. The information regarding to the reproductive health of buffalo bull is meager for breeding soundness evaluation. The venereally transmitted infections cause early embryonic death and infertility or sterility in both male and female buffaloes. To avoid these infective conditions, proper and careful investigation of reproductive tract, evaluation of semen and treatment are essential.